The textile sector of Santa Catarina at BM&FBOVESPA (Revista Brasileira de Contabilidade e Gestão, 2013)
This article presents a perspective of the textile sector in Brazil, with the main objective of identifying the profile of textile sector companies of Santa Catarina listed on the BM&FBOVESPA. The methodology used for the research was classified as exploratory, documentary, and qualitative. A total of eight of the 19 companies listed on the BM&FBOVESPA in the yarn, fabric, and clothing segments are from the State of Santa Catarina, in the Vale do Itajaí region. The net revenue generated by these eight companies corresponds to 54.61% of the total net revenue of the companies listed in these segments and they employ about 11,300 employees. The time of operation of textile sector companies of Santa Catarina listed on the BM&FBOVESPA also analyzed, which showed that Cia Hering is the oldest, with 133 years, and Teka Tecelagem Kuehnrich S.A., is the most recent, founded in 1926, with 87 years of existence. The main products of the region are clothing items, flat and knitted fabrics, fluffy articles, bed and table items, yarn, hospital textiles, elastic tapes, and woven labels.
Keywords: textile sector; Santa Catarina; BM&FBOVESPA